POWERFUL TOOLS FOR TEACHING AND LEARNING: DIGITAL STORYTELLING - Sawiji, Bekti (Universitas Nusantara PGRI Kediri, 2016)
Digital storytelling is the telling of stories using computer-based tools to tell stories. It combines the art of telling stories with a variety of multimedia, including graphics, audio, video, and Web publishing. In the field of education, teachers and their students, from early childhood classrooms through graduate school, are using digital storytelling in many different content areas and across a wide range of grade levels. The purpose of this article is to explain the way how the digital storytelling can be created. There are five steps in creating digital storytelling in this workshop. 1. Determine Topic and Write a Script, 2. Collect Digital Resources, 3. Select Content and Develop a Storyboard, 4. Import, Record, Finalize, and 5. Share, Teach, Improve. It is expected that after having completed reading this article, the readers can create their own digital storytelling for educational use. Key Words: Digital Storytelling, Computer Based Tools